Within-Season Producer Response to Warmer Temperatures: Defensive Investments by Kenyan Farmers. Issue 633 (26th May 2020) - Jagnani, Maulik; Barrett, Christopher B; Liu, Yanyan; You, Liangzhi
Abstract: We present evidence that farmers adjust agricultural inputs in response to within-season temperature variation, undertaking defensive investments to reduce the adverse agro-ecological impacts of warmer temperatures. Using panel data from Kenyan maize-growing households, we find that higher temperatures early in the growing season increase the use of pesticides, while reducing fertiliser use. Warmer temperatures throughout the season increase weeding effort. These adjustments arise because greater heat increases the incidence of pests, crop diseases and weeds, compelling farmers to divert investment from productivity-enhancing technologies such as fertiliser to adaptive, loss-reducing, defensive inputs such as pesticides and weeding labour.